Configuration Design and Kinematics Analysis of a New 4-DOF Parallel Machine Tool - Liuyuan He; Ying Mei; Wenwen Xu; Zuo Shen; Ruiqin Li (Jixie chuandong)
A new 4-DOF partially decoupled parallel mechanism which can move along the y-axis， z-axis and rotate around the x-axis and y-axis is proposed. The mechanism is supplemented by a moving platform which can move the x-axis and rotate the x-axis of the spindle. The mechanism is designed for machining turbine blades. The kinematics analysis of the mechanism carried out， the kinematics equation and Iacobian matrix are obtained. The workspace of the mechanism is analyzed by using the geometric method， the Jacobian matrix is used to prove that the scheme has no singularities in its workspace， the required stroke length of the actuator for the defined task is obtained.